HSF1-mediated regulation of tumor cell apoptosis: a novel target for cancer therapeutics. (October 2013) - Kumar, Sanjay; Tomar, Munendra Singh; Acharya, Arbind
Programmed cell death/apoptosis is a genetically conserved phenomenon involved in many biological processes including reconstruction of multicellular organisms and elimination of old or damaged cells. It is regulated by the activation/deactivation of PKC in response to exogenous and endogenous stimuli. PKC is activated under stress by a series of downstream signaling cascades, which ultimately induce HSF1 activation, which results in overexpression of heat shock proteins. Overexpression of heat shock proteins interferes in the apoptotic pathway, while their blocking results in apoptosis. Therefore, HSF1 could be a novel therapeutic target against a variety of tumors. Several pharmacological inhibitors of PKC have been demonstrated to exert inhibitory effects on the activation of HSF1 and, therefore, induce apoptosis in tumor cells. However, studies regarding the role of pharmacological inhibitors in the regulation of apoptosis and possible anti-tumor therapeutic intervention are still unknown or in their infancy. Therefore, an attempt has been made to delineate the precise role of HSF1 in the regulation of apoptosis and its prospects in cancer therapeutics.